Pop Cult: Religion and Popular Music, by Rupert Till. Continuum, 2010. 230pp., Hb. $120.00, ISBN-13: 9780826445926; Pb. $34.95, ISBN-13: 9780826432360. - Cusack, Carole M. (International Journal for the Study of New Religions, 2014)
Book review